INTEGRATIVE SCIENTIFIC MADRASAH IN INDONESIA: New Developments in Integrating Science and Religion in the Learning Processes - ANGGUN ZUHAIDA (Islam Futura, 2018)
Science and religion are a unity. The difference between the two lies only in the way of view. Knowledge comes from the One God. All kinds of approaches to reality are ultimately capable of being integrated and integrated with the contemplation of the concept of God's oneness. Scientific activity is closely related to the implementation of education. The implementation of education is always based on curriculum development. The existence of curriculum development is based on the emergence of future challenges and competencies. This research aims to describe the design of integrative science and religion in the device and the implementation of learning. The research method used is descriptive qualitative, sample in this research is teacher at MTsN Kota Salatiga. The integration of science and religion is seen only in the implementation of learning, where teachers have introduced the relationship of science and religion through connecting with the verses of the Qur'an. The integration that has been implemented in the madrasah is already on the operational level.